2013
DOI: 10.1002/ece3.739
|View full text |Cite
|
Sign up to set email alerts
|

Dioecy, more than monoecy, affects plant spatial genetic structure: the case study of Ficus

Abstract: In this analysis, we attempt to understand how monoecy and dioecy drive spatial genetic structure (SGS) in plant populations. For this purpose, plants of the genus Ficus were used as a comparative model due to their particular characteristics, including high species diversity, variation in life histories, and sexual systems. One of the main issues we assessed is whether dioecious fig tree populations are more spatially genetically structured than monoecious populations. Using the Sp statistic, which allows for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 108 publications
(265 reference statements)
2
53
2
Order By: Relevance
“…Nevertheless, Nazareno et al (2013) stated that dioecy may significantly contribute to spatial genetic structure (SGS) in natural populations of dioecious plants. Dioecious plant species analyzed by the authors had on average 6-fold higher SGS than monoecious species.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…Nevertheless, Nazareno et al (2013) stated that dioecy may significantly contribute to spatial genetic structure (SGS) in natural populations of dioecious plants. Dioecious plant species analyzed by the authors had on average 6-fold higher SGS than monoecious species.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…In effect, in many dioecious species SGS can be more pronounced compared with monoecious plants. However, although dioecy is generally recognised as an important factor of SGS (Barluenga et al, 2011;Nazareno et al, 2013), to our knowledge the role of sex ratios has not been thoroughly addressed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparative study showed that dioecious Ficus species tend to exhibit stronger SGS than monoecious congeners (Nazareno et al, 2013). The authors identified several factors that might be responsible for shaping different potentials for long-distance pollen dispersal in dioecious and monoecious fig species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies from amplified fragment length profiles (AFLPs), RAPDs, and microsatellites detected low to moderate levels of genetic diversity (Travis and Sheridan, 2006;Larkin et al, 2008;Larkin et al, 2017) Halodule wrightii population differentiation was first detected in the Texas region as following the genetic isolation-by-distance model (Travis and Sheridan, 2006;Larkin et al, 2008). This result is unsurprising given that H. wrightii seeds are negatively buoyant and are released at the sediment surface, encouraging local dispersal, and that dioecious plants such as seagrasses are more likely to experience isolation-by-distance genetic structuring than monoecious plants (Nazareno et al, 2013). However, isolation-by-distance in seagrasses is highly regionally specific (Muñez-Salazar et al, 2005), and later study showed population structure in the region was more closely related to tidal range than to barriers or distance (Larkin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%